Post Fraud: An Empirical Study of Firms In Malaysia - Puat Nelson, Sherliza (International Scholar Journals, 2012)
The paper specifically examines the post fraud firms’ characteristics for over 3 years after fraud had occurred. Selections of companies were made from Securities Commissions’ enforcement actions released between the years 2000 until 2008. A matched pair sampling was made with the control group, and 256 firms’ observations were made. Findings revealed declining sales as well as increased in debts during the three years after the fraud for fraud firms. However, roles of block holders and board’s size may lessen the impact of fraud.